Influence of menstrual- and hormonal contraceptive cycle on self-reported symptom severity and recovery measures across an annual season in female endurance athletes: The FENDURA project - Engseth, T. P.; Osborne, J. O.; Solli, G. S.; Morseth, B.; Andersson, E. P.; De Martin Topranin, V.; Taylor, M.; Noordhof, D. A.; Sandbakk, Ø.; Welde, B. (Journal of Sports Sciences, 2025)
This longitudinal study investigated 1) differences in self-reported cycle-related symptom severity and recovery measures (sleep quality, readiness to train, resting heart rate) between pre-bleeding, bleeding, and non-bleeding days in athletes using/not using hormonal contraception (HC); 2) associations between symptom severity and recovery measures. Fifty-eight female endurance athletes recorded recovery measures, perceived symptom severity, and menstruation/withdrawal (bleeding) days for one year. Athletes were grouped as: intrauterine system (IUS)-, implant-, progestin-only oral contraceptive (POC)-, combined oral contraceptive (COC)- and non-HC users. All groups reported higher symptom severity during bleeding compared to pre-bleeding and non-bleeding days (both p < .001), while implant users reported less severe symptoms than IUS (p < .001) and non-HC users (p = .008). Perceived sleep quality was lower during pre-bleeding compared to bleeding days (p < .001) for all groups. However, IUS users reported higher sleep quality (p = .039) and physical readiness-to-train (p = .010) than non-HC users. Symptom severity was negatively associated with sleep quality and physical readiness-to-train (both p < .050). Pre-bleeding days and cycle-related symptom severity were found to negatively influence self-reported recovery measures in both HC- and non-HC users. Therefore, athletes and their support staff are advised to prioritize symptom management and the adjustment of recovery strategies on an individual basis throughout the athletes` cycles.